DEVELOPMENTAL CHARACTERISTICS OF EMOTIONAL SELFREGULATION IN INFANCY - Ato Lozano, Ester; González Salinas, Carmen; Carranza Carnicero, José Antonio (Anales de Psicología / Annals of Psychology, 2004)
Several approaches to the study of self-regulation define it as the ability of the individuals to modify one's behavior in responding to the demands of specific situations. In this field, emotional self-regulation in infancy has gained interest in the last years because of its implications for different areas of individual development, especially social functioning. In the development of emotional selfregulation in infancy, exogenous factors have been identified, with a special emphasis on the maturation of the attentional networks. Concerning to exogenous factors, parents have been given an importante role in guiding the development of their children. On another hand, individual differences found in emotional self-regulation seem to be temperamentally based.